2017
DOI: 10.1111/evo.13284
|View full text |Cite
|
Sign up to set email alerts
|

Out of the dark: 350 million years of conservatism and evolution in diel activity patterns in vertebrates

Abstract: Many animals are active only during a particular time (e.g., day vs. night), a partitioning that may have important consequences for species coexistence. An open question is the extent to which this diel activity niche is evolutionarily conserved or labile. Here, we analyze diel activity data across a phylogeny of 1914 tetrapod species. We find strong phylogenetic signal, showing that closely related species tend to share similar activity patterns. Ancestral reconstructions show that nocturnality was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
131
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(144 citation statements)
references
References 77 publications
(173 reference statements)
10
131
3
Order By: Relevance
“…As opposed to the other strategies, the nocturnal strategy is dominated by a specific clade – the Gekkota (Appendix S9), although it contains members of other clades as well (notably Australian Lerista skinks). This finding is compatible with previous studies that found that diel activity is highly phylogenetically conserved (Anderson & Wiens, ; Roll, Dayan, & Kronfeld‐Schor, ; Vidan et al, ). This raises two interesting questions for future research: (a) Why does nocturnality seldom occur in the New World; and (b) Why does nocturnality remain almost exclusively (94% of species) a gekkotan trait?…”
Section: Discussionsupporting
confidence: 93%
“…As opposed to the other strategies, the nocturnal strategy is dominated by a specific clade – the Gekkota (Appendix S9), although it contains members of other clades as well (notably Australian Lerista skinks). This finding is compatible with previous studies that found that diel activity is highly phylogenetically conserved (Anderson & Wiens, ; Roll, Dayan, & Kronfeld‐Schor, ; Vidan et al, ). This raises two interesting questions for future research: (a) Why does nocturnality seldom occur in the New World; and (b) Why does nocturnality remain almost exclusively (94% of species) a gekkotan trait?…”
Section: Discussionsupporting
confidence: 93%
“…Differences in sample numbers between the analyses can be explained by either too low RNA yield for gene expression analysis or failed runs on the flow cytometer during fieldwork. Pagel's λ was calculated for all variables to determine the strength of the phylogenetic signal for each parameter (Pagel 1999;Münkemüller et al 2012;Cooper et al 2016;Anderson and Wiens 2017) (R package PHYTOOLS, command phylosig (Revell 2012)).…”
Section: Discussionmentioning
confidence: 99%
“…At larger scales it may compete with genetic constraints or biogeographic contingencies. As an example, Peixoto et al () find climatic (β‐) niche conservatism among bats at the level of order or family, but not at lower levels. The same pattern was found in the geophylogenetic patterns of Floridian plant communities (Cavender‐Bares et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors have found the opposite pattern, i.e. α ‐niche conservatism (Richman and Price , Ackerly et al 2006, Sallan and Friedman , Muschick et al 2014, Anderson and Wiens ), and sometimes there is no clear signal (Ingram and Shurin , Bernard‐Verdier et al 2013).…”
Section: Introductionmentioning
confidence: 98%